Doing business and inclusive human development in Sub-Saharan Africa. Issue 1 (17th September 2018) - Asongu, Simplice; Odhiambo, Nicholas
Abstract : Purpose: The purpose of this paper is to examine how doing business affects inclusive human development in 48 Sub-Saharan Africa for the period 2000–2012. Design/methodology/approach: The measurement of inclusive human development encompasses both absolute pro-poor and relative pro-poor concepts of inclusive development. Three doing business variables are used, namely: the number of start-up procedures required to register a business, time required to start a business, and time to prepare and pay taxes. The empirical evidence is based on fixed effects and generalised method of moments regressions. Findings: The findings show that increasing constraints to the doing of business have a negative effect on inclusive human development. Originality/value: The study is timely and very relevant to the post-2015 Sustainable Development Agenda for two fundamental reasons: first, exclusive development is a critical policy syndrome in Africa because about 50 per cent of countries in the continent did not attain the Millennium Development Goal extreme poverty target despite enjoying more than two decades of growth resurgence. Second, growth in Africa is primarily driven by large extractive industries and with the population of the continent expected to double in about 30 years, scholarship on entrepreneurship for inclusive development is very welcome. This is essentially because studies have shown that the increase in unemployment (resulting from the underlying demographic change) would be accommodated by the private sector, not the public sector.